Mobilitas sosial di Era teknologi digital AI: Peluang dan tantangannya di Indonesia - Zufar Sabiq, Muhammad; Khasanah, Nur (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
The development of digital technology has brought about significant transformations in the dynamics of social mobility in Indonesia. Digitalization not only creates new opportunities for improving social status through access to education, employment, and the digital economy, but also presents structural challenges that widen the social gap between groups with high digital literacy and those left behind. This phenomenon demands a critical analysis of how digital technology becomes an instrument for vertical and horizontal social mobility, and the extent to which public policy is able to accommodate the resulting social changes. Through theoretical and empirical studies, this research aims to identify opportunities and obstacles in utilizing digital technology as a means of social mobility in Indonesia, taking into account aspects of education, the economy, and social equality.